Conformational and vibrational study of platinum(II) anticancer drugs: cis-diamminedichloroplatinum (II) as a case study - Amado, Ana M. (2007)
A conformational and vibrational analysis of cisplatin [cis-diamminedichloro-platinum(II)] (cDDP) is reported. Several theory methods (from Hartree-Fock to Moller-Plesset and density functional theory) combined with different all-electron basis sets are evaluated, in view of determining the best suited strategy for accurately representing this molecule. This choice is based on the best compromise between accuracy and computational requirements. Different scaling models of the cDDP vibrational modes were tested for obtaining the best scaling factors to be used in this type of inorganic systems. The structural parameters and vibrational results predicted by the calculations are compared with the corresponding experimental data, namely, x-ray structure, and Raman and inelastic neutron scattering spectra. Finally, a complete assignment of the cDDP vibrational spectra is presented.